The Influence of Product Quality and Price on Customer Loyalty Through Brand Image as A Mediation Variable on Consumers Of "B_ERL COSMETIC" Products in Shopee Marketplace - Titis Tatasari; Ahmad Rizki Sridadi; Dian Ekowati (International Journal of Economics Accounting and Management, 2024)
This study wants to find out how the quality and price of B_Erl Cosmetics affect whether customers keep buying their products on Shopee. This study used a numbers-based method to figure out how the variables are related. This study looked at 100 customers who use Shopee. The customers were all women who are at least 17 years old and have made at least 2 purchases on the B_Erl Cosmetic Shopee page. Collecting information in research using watching and asking questions. The tools we used to analyze data for our research were SPSS 26 software and Calculator Sobel Test to figure out the indirect effect. This research used a method called path analysis to analyze the data. The results we found showed that the quality and price of the product have some impact on how people see the brand. Also, the quality, price, and brand image have an effect on how loyal customers are to the brand. The quality of the product has an impact on customer loyalty through the brand image, and the price also has an impact on customer loyalty through the brand image.